Comparative analysis of positive output super lift DC-DC luo converters - Richa Adlakha; Anita Khosla; Dheeraj Joshi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Due to the advancement in the semiconductor technologies, DC-DC converters are gaining the importance in several industrial applications. They form the core of the switched mode power supplies which are used in real time applications. The performance of the conventional converter is affected by the parasitic elements and their voltage gain is also limited. To improve upon this, Super lift converters converter were developed by Luo. Voltage lift technique increases the voltage in geometric progression .These super lift converter are classified as positive output and negative output which are further classified into different series. In this paper series of Positive output Super lift converter topologies are analyzed. The proportional –integral controller is employed to theses converter in the paper. These converters boost the voltage up to three times the input voltage and gaining importance in Electric vehicles and Solar powered applications. The simulations are carried in PSIM.